400 Oscillation Transmission and Ventilation during Face Mask-Delivered High Frequency Oscillatory Ventilation in Infants: a Bench Study with Active Lung Simulator. (October 2012) - Luca, D De; Costa, R; Spinazzola, G; Cipriani, F; Piastra, M; Conti, G
Abstract : Background: Noninvasive high frequency oscillatory ventilation (nHFOV) has been applied through nasal prongs as a new respiratory technique in preterm neonates and has been found to reduce CO2, but it has never been studied in bigger infants. Its mechanical properties when applied through a face mask are not known. Methods: We modeled the application of face mask-NHFOV in infants using a pediatric mannequin connected to an active lung simulator (ASL5000). This was set mimicking the mechanical properties of a normal lung (Crs 1 mL/cmH2 O/Kg; Raw: 40 cmH2 O/L/sec; Pmus 6 cmH2 O; rate: 40 breaths/min) in a male infant at 1 year, 8 Kg, 3 rd percentile for age. NHFOV parameters were sequentially changed. Spontaneous tidal volume (sTv), oscillatory stroke volume (oTv) and oscillation amplitude (DeltaPdist) at the lung simulator were recorded. Oscillatory pressure ratio (OPR: DeltaPdist/DeltaP) and the theoretical ventilation during HFOV (DCO2=frequency x oTv 2 ) were also calculated. Results: Mean oTv, OPR and DCO2 were 1.9±0.7 mL/Kg, 0.05±0.02 and 221±136 Hz x mL 2 /Kg, respectively. Significant correlations were found between OPR and oTv ( r =0.48; p <0.001) and OPR and DCO2 ( r = 0.47; p <0.001).oTv significantly correlates with sTv (r=0, 885; p<0, 001). At a multivariate regression OPR was the factor more strongly associated with oTv (st.β=0.88) and DCO2 (st.β=0.96; p<0.001). Discussion: NHFOV through face mask is feasible. Oscillation amplitude is dampened by the interface and may reach in the lung 11% of the set value.Nonetheless, in this model adequate Tv and DCO2 are reached and OPR was the factor more strongly influencing ventilation.